Time for Fishing: Bargaining Power in the Baltic Swedish Cod Fishery - Johan Blomquist; Cecilia Hammarlund; Staffan Waldo (Lund University, School of Economics and Management, Department of Economics, 2013)
How are market conditions affected by a change in fishery regulations? Who benefits and who loses? The paper discusses the price effects of a reform in the Swedish Baltic cod fishery where vessels using active gear were given annual quotas rather than the previously applied quarterly quotas. We investigate whether the bargaining power of fishers using trawlers have improved after the reform using a difference-in-difference approach. Since fishers have more freedom to fish for cod over the year and processors are keen to have regular landings of fish (in order not to have unused capital), we suggest that prices are likely to increase following the reform. The results indicate that prices have increased due to the increased bargaining power of fishers after the reform. We control for the effects of fish size, fish quality, landing port and landing date. We also investigate whether the price change that we have found is driven by changes in reservation prices and find that this is not the case. Thus, we conclude that introducing yearly quotas is likely to have changed bargaining power between fishers and buyers in the Swedish Baltic cod fishery.
Keywords: D47; Q21; Q22; 330; Bargaining power; Difference-in-difference; Fishery management; Baltic Cod